Organizational analysis of the seed sector of rice in Guinea: stakeholders, perception and institutional linkages - Florent, O.; Mele, P. van; Nuijten, E.; Struik, P.C.; Mongbo, R. (Cambridge University Press, 2011)
This paper analyses the organization of the rice seed sector in Guinea with the overall objectives to assess how organizational settings affect seed supply to small-scale farmers and to suggest institutional changes that would favour seed service and uptake of varieties. Data were collected in Guinea, West Africa, using focus group discussions with extension workers, farmers, representatives of farmers’ associations, agro-input dealers, researchers and non-governmental organization (NGO) staff, and surveys of 91 rice farming households and 41 local seed dealers. Findings suggest that the current institutional settings and perceptions of stakeholders from the formal seed sector inhibit smallholder farmers’ access to seed. Seed interventions in the past two decades have mainly relied on the national extension system, the research institute, NGOs, farmers’ associations and contract seed producers to ensure seed delivery. Although local seed dealers play a central role in providing seed to farmers, governmental organizations operating in a linear model of formal seed sector development have so far ignored their role. We discuss the need to find common ground and alternative models of seed sector development. In particular we suggest the involvement of local seed dealers in seed development activities to better link the formal and the informal seed systems and improve smallholder farmers’ access to seed from the formal sector